The Impact of Institutional Pressures on the Adoption and Maintenance of E-commerce in Brazilian Micro and Small Enterprises (MSEs) - Adriano de Sousa, Henrique; Klein, Luciana; Bernardes Voese, Simone (Review of Business Management, 2022)
Objective – Amid the technological rise and late adhesion by micro and small companies, the study aims to verify the impact of institutional pressures on the perception of barriers and benefits in the adoption and maintenance of e-commerce in Brazilian MSEs. Theoretical framework – The study was developed based on the precepts of Institutional Theory, aimed at approaching institutional pressures, verifying how the orientation and adaptation of the actions taken by MSEs towards the use of e-commerce as an organizational practice occurs. Methodology – The research was carried out from a survey with 120 e-commerce managers, using a questionnaire composed of 28 statements about institutional pressures in e-commerce, perceived benefits and barriers, in addition to aspects related to adoption and e-commerce maintenance. For data analysis, structural equation modeling was applied. Results – The results demonstrate that mimetic and normative institutional pressures provide the perception of benefits and help to overcome barriers in relation to e-commerce, leading companies to adopt and improve this business modality. On the other hand, coercive pressures did not indicate an association with the perception of benefits, but mitigated the perception of barriers, suggesting that coercive pressures are motivated according to the context of the country in which they are inserted. Contributions – There is an advance in the discussion of Institutional Theory, in which it is possible to verify that institutional pressures influence MSEs to join and maintain new forms of online business. In this way, the results guide managers in the development of strategies using digital technologies as competition tools. Keywords - E-commerce; MSEs; Adoption and Maintenance; Institutional pressures; Barriers and Benefits.